Early steps in inner ear development: induction and morphogenesis of the otic placode - Sai, Xiaorei; Ladher, Raj K. (Frontiers in Pharmacology, 2015)
Various cellular replacement therapies using in vitro generated cells to replace damaged tissue have been proposed as strategies to alleviate hearing loss. All such therapies must involve a complete understanding of the earliest steps in inner ear development; its induction as a thickened plate of cells in the non-neural, surface ectoderm of the embryo, to its internalization as an otocyst embedded in the head mesenchyme of the embryo. Such knowledge informs researchers addressing the feasibility of the proposed strategy and present alternatives if needed. In this review we describe the mechanisms of inner ear induction, concentrating on the factors that steer the fate of ectoderm into precursors of the inner ear. Induction then leads to inner ear morphogenesis and we describe the cellular changes that occur as the inner ear is converted from a superficial placode to an internalized otocyst, and how they are coordinated with a particular emphasis on how the signalling environment surrounding the inner ear influences these processes.